Studi penerapan perencanaan pembangunan berbasis e-Planning di Pemerintah Kota Jambi - Tawaffal, Fernada; Delis, Arman; Junaidi, Junaidi (Jurnal Paradigma Ekonomika, 2020)
This study aims to: 1) analyze the alignment of the stages of preparation of development planning documents between the menus contained in e-Planning and the contents listed in the Regulation of the Minister of Home Affairs Number 54 of 2010; 2) analyze the influence of human resources, the commitment of policymakers, infrastructure, and information systems on the success of the Jambi City Government in implementing e-Planning-based development planning. Data is collected through surveys. The analysis tool uses logistic regression. The results showed that the level of alignment reached more than 75%. It indicates that the process of making and implementing the e-Planning application has referred to the regulation. Based on the results of logistic regression analysis, it shows that partially, the commitment of policymakers, infrastructure, and information systems significantly influences the success of e-Planning implementation